Workation as a new mode of work – analysis of top European destinations - Wąsowicz-Zaborek, Elżbieta (Bulletin of Geography. Socio-economic Series, 2025)
This study investigates the rise of workation, combining work and vacation, and evaluates 20 European cities as remote work destinations. Using k-means cluster analysis, cities were grouped based on factors such as cost of living, safety, coworking spaces, climate, internet speed, and tourist arrivals. The analysis identified four distinct clusters: cities like London with high costs and infrastructure, affordable cities such as Timișoara and Rijeka that appeal to budget-conscious workers, cities like Barcelona and Lisbon offering a balance of infrastructure and cost, and quieter, emerging hubs with moderate tourist numbers. The findings emphasize the importance of coworking spaces, affordability, and digital infrastructure in shaping workation preferences. These insights offer valuable guidance for city planners and tourism stakeholders in attracting remote workers and promoting regional economic growth by optimizing their city's workation appeal.